Literature review on domestic subcontractor selection in the Malaysian construction industry - Abdul Aziz, Nur 'Izzati; Hasan, Sharina Farihah; Abdul Rashid, Khairuddin (2015)
Subcontracting is a long-established practice in the construction industry to capitalize on the skills of trade specialists and to cope with the fluctuating construction demand. The main contractors relying so much on subcontractors to perform portion of works in construction projects that their performance may have significant effects to the overall construction project. Some past studies have highlighted common criteria in subcontractor selection. However, in order to fulfill the current needs of the industry, new list of criteria need to be identified. This paper aims to report an on-going study on domestic subcontractor selection in the Malaysian construction industry for private sector. Through literature review, it was found that bid price, financial status, adequacy of resources, experience in similar works, current commitment/workload, etc. are among the common criteria in subcontractor selection and some additional potential criteria such as sustainable construction, international standards and ethical business behavior worth to be considered.